Employment of Flake Ice Systems Including Natural Preservative Compounds for the Quality Enhancement of Chilled Seafood-A Review - Santiago P. Aubourg (MDPI AG, 2021)
Marine species deteriorate rapidly post-mortem as a consequence of a variety of biochemical and microbial breakdown mechanisms. Due to the increasing demand for high-quality fresh seafood, different strategies are now available to retard spoilage for as long as possible. The present study provides an overview of a recently proposed strategy based on the addition of natural compounds to marine species. In this strategy, different kinds of natural preservative compounds are included in the flake-ice medium that is commonly used for chilled storage. Natural sources tested for this purpose include low-molecular-weight organic acids and different kinds of extracts of plants, macroalgae, and by-products resulting from marine species commercialization. The preservative action of such treatments is analyzed according to the effect on different deteriorative mechanisms (i.e., lipid hydrolysis, oxidation, and microbial activity development), as well as on the resulting sensory acceptability and shelf-life time. The basic objective of this review is to provide an overview concerning the positive effect that the presence in an icing system of natural preserving compounds may have on the quality of chilled marine species. Furthermore, various potential avenues are proposed to develop the practical and commercial employment of this technological strategy.